2018
DOI: 10.3390/ma11102014
|View full text |Cite
|
Sign up to set email alerts
|

Design of a 2 DOFs Mini Hollow Joint Actuated with SMA Wires

Abstract: Shape memory alloys (SMAs) are smart materials used in robotics because of its light weight and high force-to-weight ratio. The low energy efficiency, up to 5%, has limited their use for large actuators. However, they have shown advantages in the design of mini-robots because of the limited volume required for the actuation system. The present study reports the design and construction of a mini compliant joint (MCJ) with a 2 degrees of freedom (DOFs) intersecting axis. The MCJ prototype has a 20 mm external di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Kinetic parameters can be evaluated via the transformations of physical specifications, such as velocity (speed, acceleration, tempo, vibration and frequency of an object's movement), path (movement pattern of transformation, such as smooth/jerky, linear/curved, continuous/intermittent or pattern/random), direction (direction in which the object moves, such as up/down, right/left and forward/backward) and space (determined by measuring the changes of scale, form or Kinesphere) (Rasmussen et al, 2012). The frequently used evaluation methods for SMA actuators are applying heat and analyzing the changes in elongation and tensile strength using a tensile testing machine (Basu and Banerjee, 1997;Manfredi and Cuschieri, 2018).…”
Section: Important Factors Of Shape Memory Alloy (Sma) As Actuatorsmentioning
confidence: 99%
“…Kinetic parameters can be evaluated via the transformations of physical specifications, such as velocity (speed, acceleration, tempo, vibration and frequency of an object's movement), path (movement pattern of transformation, such as smooth/jerky, linear/curved, continuous/intermittent or pattern/random), direction (direction in which the object moves, such as up/down, right/left and forward/backward) and space (determined by measuring the changes of scale, form or Kinesphere) (Rasmussen et al, 2012). The frequently used evaluation methods for SMA actuators are applying heat and analyzing the changes in elongation and tensile strength using a tensile testing machine (Basu and Banerjee, 1997;Manfredi and Cuschieri, 2018).…”
Section: Important Factors Of Shape Memory Alloy (Sma) As Actuatorsmentioning
confidence: 99%
“…Limitation in the mechanical bandwidth has been reported for large applications because of the slow time required to dissipate the accumulated heat. In recent studies, Manfredi et al [26][27][28][29] reported high mechanical bandwidth for the design of a mini actuator with thin SMA wires, 75µm and 100µm in diameter. Legged MRC has been designed by using SMA [30].…”
Section: On-board Locomotionmentioning
confidence: 99%
“…For those applications, the shape memory actuator must be able to generate different strokes besides the two positions "fully activated" and "fully reset" [23][24][25]. Several approaches were investigated using different control schemes to solve this problem [26][27][28][29][30][31]. Further approaches investigate the energy consumption of SMA actuators activated via Joule heating in order to keep SMA actuators attractive for miniaturization [32].…”
Section: Introductionmentioning
confidence: 99%